The Function of microRNAs in Pulmonary Embolism: Review and Research Outlook - Luo, Mingyao; Du, Mingyuan; Shu, Chang; Liu, Sheng; Li, Jiehua; Zhang, Lei; Li, Xin (Frontiers in Pharmacology, 2021)
Pulmonary embolism (PE) is a common pathologic condition that frequently occurs in patients with deep venous thrombosis. Severe PE may critically suppress cardiopulmonary function, thereby threatening the life of patients. Chronic pulmonary hypertension caused by PE may lead to deterioration of respiratory dysfunction, resulting in complete disability. MicroRNAs (miRNAs) are a group of abundantly expressed non-coding RNAs that exert multiple functions in regulating the transcriptome via post-transcriptional targeting of mRNAs. Specifically, miRNAs bind to target mRNAs in a matching mechanism between the miRNA seed sequence and mRNA 3ʹ UTR, thus modulating the transcript stability or subsequent translation activity by RNA-induced silencing complex. Current studies have reported the function of miRNAs as biomarkers of PE, revealing their mechanism, function, and targetome in venous thrombophilia. This review summarizes the literature on miRNA functions and downstream mechanisms in PE. We conclude that various related miRNAs play important roles in PE and have great potential as treatment targets. For clinical application, we propose that miRNA biomarkers combined with traditional biomarkers or miRNA signatures generated from microchips may serve as a great predictive tool for PE occurrence and prognosis. Further, therapies targeting miRNAs or their upstream/downstream molecules need to be developed more quickly to keep up with the progress of routine treatments, such as anticoagulation, thrombolysis, or surgery.